Exploring Minimum Secondary Injury for the Treatment of Ocular Trauma With Giant Intraocular Foreign Bodies - Ma, Jing; Zhang, Xiaofang; Jin, Xuemin; Wang, Wenzhan (Frontiers in Medicine, 2022)
Purpose To evaluate the method of minimum secondary injury in clinical therapy for giant intraocular foreign body (IOFB) injury. Method We retrospectively analyzed the data of 73 eyes of 73 cases of ocular trauma with giant IOFBs from Jan. 2016 to Dec. 2018. Results The giant IOFBs were 46 magnetic and 27 nonmagnetic ones. The shape was thin and flat in 19 cases, thick and flat in 12 cases, long and slender in 7 cases, thick and irregular in 35 cases. The IOFB were extracted through limbus incision path in 18 cases, pars plana path in 27 cases and the entrance wound path in 28 cases. The postoperative BCVA was increased comparing with the preoperative one (P<0.01). The postoperative BCVA in thin and flat FB group and that in long and slender group were better than that in the thick and flat shape group and thick and irregular group respectively (P<0.05). The rate of silicone oil removal in the thick and irregular group was lower than that in each of the other three groups (P<0.05). The length and the width of the IOFBs in the pars plana path group were statistically lower than that in the limbus path group (all P<0.05), and the preoperative BCVA of the pars plana path group was superior to that of the limbus path group (P<0.05). The length and the width of the IOFBs and the length of the entrance wounds in the pars plana path group were statically lower than that in the entrance wound path group (P<0.05). The postoperative BCVA in the pars plana path group was not superior to the other two groups (P>0.05). The postoperative BCVA of the entrance wound path group was statically superior to that of the limbus path group (P=0.04), while there was no difference between the two groups in the length and width of IOFBs, the length of entrance wounds or the preoperative BCVA( P>0.05). Conclusion The surgery plan of giant IOFBs should be made by the rule of minimizing secondary injury, under the consideration of ocular damage and the shape, size and location of IOFBs.